Clinical evaluation of the efficacy of the P2X7 purinergic receptor antagonist AZD9056 on the signs and symptoms of rheumatoid arthritis in patients with active disease despite treatment with methotrexate or sulphasalazine. Issue 10 (10th September 2012) - Keystone, Edward C; Wang, Millie M; Layton, Mark; Hollis, Sally; McInnes, Iain B; ,
Abstract : Objectives: The P2X7 purinergic receptor antagonist AZD9056 was evaluated in a phase IIa study and subsequently in a phase IIb study to assess the effects of orally administered AZD9056 on the signs/symptoms of rheumatoid arthritis (RA), with American College of Rheumatology 20% response criteria (ACR20) as the primary outcome. Methods: Both studies were randomised, double-blind, placebo-controlled, parallel-group studies in patients with RA receiving methotrexate or sulphasalazine. Phase IIa was an ascending-dose trial in two cohorts (n=75) using AZD9056 administered daily over 4 weeks. Phase IIb included an open-label etanercept treatment group. Patients were randomised to receive treatment for 6 months with 50, 100, 200 or 400 mg AZD9056 (oral, once a day) or matching placebo (oral, once a day), or subcutaneous etanercept (50 mg once a week). Results: In phase IIa, 65% of AZD9056 recipients at 400 mg/day responded at the ACR20 level compared with 27% of placebo-treated patients. A significant reduction in swollen and tender joint count was observed in the actively treated group compared with placebo, whereas no effect on acute-phase response was observed. Of 385 randomised patients in the phase IIb study, 383 received treatment. AZD9056 (all doses) had no clinically or statistically significant effect on RA relative to placebo as measured by the proportion of patients meeting the ACR20 criteria at 6 months and further supported by secondary end points. In both studies AZD9056 was well tolerated up to 400 mg/day. Conclusions: AZD9056 does not have significant efficacy in the treatment of RA, and the P2X7 receptor does not appear to be a therapeutically useful target in RA. Trial registration number: ClinicalTrials.gov NCT00520572 .